Tax and Regulatory Motivations for Issuing Non‐voting, Non‐convertible Preferred Stock - Callahan, Carolyn M.; Shaw, Wayne H.; Terando, William D. (Journal of Accounting Research, 2001)
This paper extends prior studies that attempt to explain the existence of unique securities, particularly Engel, Erickson, and Maydew [1999], by investigating why firms issue non‐voting, non‐convertible preferred stock (PS) instead of other securities. We find that the choice of PS is influenced by tax and regulatory changes imposed by the Tax Reform Act of 1986 (TRA86) and the 1989 Basle Banking Accord as well as various firm specific incentives. We find that industrials issue PS to preserve tax attributes by avoiding an ownership change and to maximize foreign tax credit utilization. In addition, we find that the regulatory requirements of the Basle Accord influence the choice by banks to issue PS. Finally, we show that although firms could have issued alternative securities that would have allowed them to achieve the same tax or regulatory goals, firm specific factors limit their ability to do so. For example, firms can also avoid triggering an ownership change by issuing straight debt, however, financial distress considerations may constrain their ability to issue additional debt. Therefore, we demonstrate that the final choice of PS is influenced by a combination of tax, regulatory, and firm specific incentives.